Distribution of Dental Fluorosis in the Southern Zone of Ecuador: An Epidemiological Study - Eleonor María Vélez-León; Alberto Albaladejo-Martínez; Paulina Ortíz-Ortega; Katherine Cuenca-León; Ana Armas-Vega; María Melo (MDPI AG, 2023)
In recent decades, the increase in fluoride exposure has raised the numbers of dental fluorosis in fluoridated and non-fluoridated communities In Ecuador, but the last national epidemiological study on DF was conducted more than a decade ago. The objective of this cross-sectional descriptive study was to determine the prevalence, distribution and severity of dental fluorosis (DF) using the Dean index in 1606 schoolchildren aged 6 to 12 years from urban and rural environments in provinces that make up the Southern Region of Ecuador. Participants met the inclusion criteria which were age, locality, informed consent document and no legal impediment. The results are presented using percentage frequency measures and chi-square associations. The prevalence of dental fluorosis was 50.1% in the areas of Azuay, Cañar and Morona Santiago, with no significant differences (x2 = 5.83, p = 0.054). The types of DF found most frequently were very mild and mild in all provinces; a moderate degree was more prevalent in Cañar (17%). There was no significant association (p > 0.05) between sex and the presence of dental fluorosis and, with respect to severity, the most frequent degree was moderate at the age of 12 years. The prevalence of dental fluorosis in the area evaluated is high, especially in the light and very light degrees, with a tendency toward moderate levels. It is necessary to carry out studies on the factors that are predisposing to the development of this pathology in the population studied. This research is an update regarding this pathology in Ecuador, so it is concluded that it is necessary to continue developing studies based on the findings obtained, thus contributing to the public health of the country.